2016
DOI: 10.1016/j.obhdp.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Culture and decision making

Abstract: a b s t r a c tThe study of culture and decision making addresses variations in how and why people from different cultures sometimes tend to decide differently. This review is organized around what is intended to be a comprehensive analysis of the distinct fundamental questions that people must answer in the process of making virtually all real-life decisions. Our emphasis was on recent developments as well as identifying important yet neglected topics (e.g., how decision episodes get started-or not, and why s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(88 citation statements)
references
References 116 publications
(138 reference statements)
2
85
1
Order By: Relevance
“…This lack of clear findings and the absence of theoretical explanations regarding the effect of national cultures on strategic issue interpretation is surprising, as psychological research on culture and decision‐making has shown that cultural differences affect several aspects of the decision‐making process, including information perceptions and interpretations (Li et al ., ; Yates and de Oliveira, ). One reason for the clearer findings in psychological research might be the approach used to capture culture.…”
Section: Background and Hypothesesmentioning
confidence: 98%
See 3 more Smart Citations
“…This lack of clear findings and the absence of theoretical explanations regarding the effect of national cultures on strategic issue interpretation is surprising, as psychological research on culture and decision‐making has shown that cultural differences affect several aspects of the decision‐making process, including information perceptions and interpretations (Li et al ., ; Yates and de Oliveira, ). One reason for the clearer findings in psychological research might be the approach used to capture culture.…”
Section: Background and Hypothesesmentioning
confidence: 98%
“…One reason for the clearer findings in psychological research might be the approach used to capture culture. While management research follows the values‐based approach, psychological research utilizes a socio‐cognitive approach to investigate the effects of culture on decision‐making (Peng and Knowles, ; Chua et al ., ; Yates and de Oliveira, ).…”
Section: Background and Hypothesesmentioning
confidence: 98%
See 2 more Smart Citations
“…EO studies were predominantly Western in nature (Covin and Slevin, 1989;Zahra and Covin, 1995;Lumpkin and Dess, 2001;Yates and Stephanie, 2016). A number of academic researchers questioned the applicability study of western practices of using similar framework to measure the degree of OC when dealings with developing countries.…”
Section: Purpose Of the Studymentioning
confidence: 99%